Graft Copolymerization of Styrene from Poly(vinyl alcohol) via RAFT Process - Gholam Ali Koohmareh; Morteza Hajian; Hazhir Fallahi (International Journal of Polymer Science)
Polystyrene, PS, was grafted from poly(vinyl alcohol), PVA, backbone by reversible addition-fragmentation chain transfer (RAFT) polymerization. The hydroxyl groups of the PVA were converted into aromatic dithioester RAFT agent and polymerization began in the presence of this agent. The structure of compounds was confirmed by FT-IR and 1HNMR spectroscopy. The graft copolymer was characterized by thermogravimetric analysis (TGA), X-ray diffraction (XRD), and scanning electron microscopy (SEM). Grafted polystyrene chains were cleaved from the PVA backbone by acidic hydrolysis of the PVA-g-PS, and its polydispersity index, PDI, was determined by gel permeation chromatography (GPC) showing narrow molecular weight distribution.